The Role of Sustainable Corporate Development and Green Accounting: Literature Review - Abdul Rahman; Muliati; Ali Supriadi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research serves summary findings from various related research with sustainability, accounting environment and responsibility answer social company (CSR). Study This covers aspects like understand case business for sustainability, practice disclosure environment company, concept accountancy management environment, relationships between CSR and performance finance, and implementation system accountancy green. Additionally, research This also discusses influence source Power organization to use accountancy management environment (environmental management accounting/EMA), implementation reporting innovation green, impact not quite enough answer environment company (corporate environmental responsibility/CER) towards innovation green company (corporate green innovation/CGI), and integration system control management with management quality and intellectual capital accounting. Study This give view holistic about concepts it and its contribution to practice sustainable business.